Analisis Hidrologi untuk Perencanaan Sistem Polder di DKI Jakarta - Segel Ginting (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
The application of the polder system for flood control in DKI Jakarta has become a must for coastal areas, especially with the construction of sea dikes along the coast of Jakarta as a solution to anticipate tidal flooding. One thing to consider when using a polder system in flood control is how much pump capacity and reservoir are needed. To answer this quetions, a hydrological analysis has been carried out with several method approaches, starting from determining the rainfall design in the form of a depth duration frequency curve in 1 hour to 48 hours, and then applied area reduction factor (ARF) to corrected rainfall design. Natural Resources Conservation Service (NRCS) method are uses to calculated runoff or effective rainfall and then with the unit hydrograph by time area method to produce a runoff hydrograph. Based on this approach, the Sentiong Polder plan has been carried out with the result that the required pump capacity for a 25-year return period is 32 m3/s and 50 m3/s for a 100-year return period with a storage capacity used of 1,507,500 m3. If you want to reduce the pump capacity, it is necessary to increase the storage capacity.